OXYGEN AS A FACILITATOR IN THE REDUCTION OF SURGICAL SITE INFECTIONS - Adeel Arsalan; Mehtab Alam; Syed Baqar Shyum Naqvi (Journal of University Medical & Dental College, 2013)
ABSTRACT: Globally surgical site infections (SSIs) are one of the most common nosocomial infections. Oxygen acts as a facilitator in the reduction of surgical site infections particularly in colorectal and abdominal surgery. During surgery the normal flora present in large intestine have also been eradicated which are the potential source of post operative infections. Supplemental oxygen aids in the eradication of pathogenic bacteria by oxidative killing. The oxidative killing not only heals the wounds but also enhances the activity of immune system by forming superoxide radicals. High fraction of inspired oxygen facilitate in reduction in the frequency of postoperative nausea and vomiting. Polymorphnuclear leukocytes also participate in the eradication of bacteria by oxidative killing. Free radicals of oxygen activate vascular endothelial growth and help in vasoconstriction. Hypoxia is one of the major problems encountered by anesthetist. Oxygen is used in combination with other gases to enhance the analgesic and anesthetic activity. Oxygen also reduces the chances of post-operative infection, nausea, and vomiting. High supplemental inspiration helps in the prevention of pneumonia. Oxygen is involved in a number of metabolic reactions. The size of the lesions and infections is reduced by an increase in the level of tissue oxygenation.